Дослідження моделі лінійного міста із зовнішньою конкуренцією - Дзюба, Є. В. (ХНУРЕ, 2024)
The linear city model, also known as the Hotelling model, is a fundamental concept in spatial economics. It explores the behaviour of firms and consumers in a spatial context, considering factors such as location, competition, and transportation costs. In this model, we envision a linear arrangement of sellers and consumers along a one-dimensional space, such as a street or highway.
Keywords: лінійне місто; зовнішня конкуренція